2021
DOI: 10.7554/elife.63396
|View full text |Cite
|
Sign up to set email alerts
|

Stretching of the retinal pigment epithelium contributes to zebrafish optic cup morphogenesis

Abstract: The vertebrate eye-primordium consists of a pseudostratified neuroepithelium, the optic vesicle (OV), in which cells acquire neural retina or retinal pigment epithelium (RPE) fates. As these fates arise, the OV assumes a cup-shape, influenced by mechanical forces generated within the neural retina. Whether the RPE passively adapts to retinal changes or actively contributes to OV morphogenesis remains unexplored. We generated a zebrafish Tg(E1-bhlhe40:GFP) line to track RPE morphogenesis and interrogate its par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…At 48 hpf, however, the staining span was no longer different from the 36 hpf SF. These data show that RPE identity is maintained in CF eyes, yet its expansion movement to cover the whole retina is delayed compared to SF – reinforcing the notion that the rim movement is impaired in cavefish and that RPE spreading could contribute to invagination forces ( Moreno-Marmol et al, 2021 preprint). Potentially, RPE spreading may also be involved in optic fissure closure, as suggested by the presence of coloboma upon impairment of the rim movement by BMP4 overexpression in the OV ( Heermann et al, 2015 ).…”
Section: Resultssupporting
confidence: 70%
“…At 48 hpf, however, the staining span was no longer different from the 36 hpf SF. These data show that RPE identity is maintained in CF eyes, yet its expansion movement to cover the whole retina is delayed compared to SF – reinforcing the notion that the rim movement is impaired in cavefish and that RPE spreading could contribute to invagination forces ( Moreno-Marmol et al, 2021 preprint). Potentially, RPE spreading may also be involved in optic fissure closure, as suggested by the presence of coloboma upon impairment of the rim movement by BMP4 overexpression in the OV ( Heermann et al, 2015 ).…”
Section: Resultssupporting
confidence: 70%
“…A bHLH transcription factor gene Bhlhe40 was reported to be expressed in the developing RPE as well as somites and other organ primordia of mice and zebrafish [ 8 , 12 ]. Recently, this gene has been used to visualize the cell behavior during early RPE development [ 7 , 9 ]. Here, we firstly described the early onset of BHLHE40 expression in the dorsal region of the optic vesicle, the prospective RPE of the chicken [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in zebrafish have shown that NR development is a default state and specification of RPE in the optic primordia separates the distinct NR and RPE domains in the optic cup [ 6 ]. However, differences between species are observed in the development of RPE: Maturation of RPE is fulfilled by cell shape change in zebrafish but in amniotes cell proliferation occurs in that phase [ 7 ]. In this study, we focus on an RPE gene, basic helix-loop-helix e40 , ( BHLHE40 ), shown to be expressed in the prospective and definitive RPE cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theoretical and practical attempts been made to show the role played by mechanics as a driver of tissue self-organization and morphogenesis [ 8 ]. Recently, attempts have been made to determine the role of RPE in the creation of the mechanical forces responsible for optic cup formation [ 117 ]. The authors managed to address this problem by genetically modifying the Tg (E1- bhlhe40 :GFP) line of zebrafish.…”
Section: Embryonic Retina Self-organization In Vivomentioning
confidence: 99%